The Amazing Spider-Man - Wells, Zeb 1977- (Marvel Worldwide, Inc., 2022)
Peter Parker is on the outs with the Avengers. He’s on the outs with the Fantastic Four. He’s on the outs with Aunt May! No one wants to see Spider-Man — except for Doctor Octopus. Doc Ock is on Spidey’s tail, and the Master Planner has something truly terrible planned for when he gets his tentacles on Spidey. But what did Spider-Man do that has alienated him from everyone? And what moves is the gangster called Tombstone making? Just in time for Spider-Man’s 60th Anniversary, a new era of AMAZING SPIDER-MAN begins, blockbuster artist John Romita Jr. returns — and 2022 is going to be the biggest year for the wallcrawler ever!
Keywords: Wolverine -- Fiktive Gestalt; Spider-Man -- Fiktive Gestalt; Entfremdung; Comic